x-(2x+5)=3x+13

Simple and best practice solution for x-(2x+5)=3x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(2x+5)=3x+13 equation:


Simplifying
x + -1(2x + 5) = 3x + 13

Reorder the terms:
x + -1(5 + 2x) = 3x + 13
x + (5 * -1 + 2x * -1) = 3x + 13
x + (-5 + -2x) = 3x + 13

Reorder the terms:
-5 + x + -2x = 3x + 13

Combine like terms: x + -2x = -1x
-5 + -1x = 3x + 13

Reorder the terms:
-5 + -1x = 13 + 3x

Solving
-5 + -1x = 13 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-5 + -1x + -3x = 13 + 3x + -3x

Combine like terms: -1x + -3x = -4x
-5 + -4x = 13 + 3x + -3x

Combine like terms: 3x + -3x = 0
-5 + -4x = 13 + 0
-5 + -4x = 13

Add '5' to each side of the equation.
-5 + 5 + -4x = 13 + 5

Combine like terms: -5 + 5 = 0
0 + -4x = 13 + 5
-4x = 13 + 5

Combine like terms: 13 + 5 = 18
-4x = 18

Divide each side by '-4'.
x = -4.5

Simplifying
x = -4.5

See similar equations:

| -5x/6+1=5/18 | | 12-5x=48 | | 11x-6=7-2x | | (235)^1/3 | | 1-6y+3=2y+10-6y | | -9=5-(7-z) | | -6(x+5)+5=-25 | | 1(x-9)=5x-4(x-1)+43 | | 5-2(y+1)=2 | | x/14+51=55 | | -11+10=-45 | | 6(4+n)= | | 5(2+v)+36v=13v | | (1/4)/(65/12)= | | f(z)=xy^2+ix^2y | | 7.4p-2.3p+3.1=33.7 | | 8x+2x=-15 | | 7(y+8)= | | 2.1x-1.1x+8.1=-0.6 | | n/5+10n+51 | | 5v/6+7/6=112 | | 0.55x+0.4=x-2 | | 6-2(4-m)=8m-3(2m+5) | | 9x+8-4x=14-x | | 132=(t*t)-T | | 3/2*-9=0 | | 2x+7=6x-6 | | 6x+8y=96 | | -4(r+6)=-55 | | (5/3)x^2-x=(4/3) | | 6-2(2-m)=8m-3(2m+5) | | -3y-5y=8 |

Equations solver categories